PERKEMBANGAN DAN SISTEM PENGANGKUTAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (B3) DI INDONESIA - Tri Mulyono; Kencana Verawati (Universitas Negeri Jakarta, 2021)
Industrial development besides having a positive impact on the economy, also has a negative impact such as the waste industry. Non-hazardous and non-toxic material waste no to be handled as strictly as hazardous and toxic material waste, although the waste industry. This issues (1) How is the development of hazardous and toxic waste transportation?; and (2) How is the hazardous and toxic waste transportation system? The response to the issues are the aims of this research. The method used is a literature study and analyzed descriptively. The results of the search for hazardous and toxic waste transportation data for the 2015–19 period and analysis shows: (1) The amount of hazardous and toxic waste in Indonesia decreasing, but the waste transportation companies increase by 40.98% (3650 waste transportation service companies) from 2589 in 2018; (2) the number of permits increased by an average of 23.58%/year; (3) the number of vehicles hazardous transporting is 8,984 vehicles or 4 times from 2015; and (5) the contributing sectors for hazardous are Mining, Energy and Oil and Gas; Manufacture; Infrastructure and Services; and Agro Industry.